Akibat Hukum Dan Psikososial Dari Perkawinan Antar Penganut Agama (Tinjauan Hukum Islam Dan Undang-Undang No.1 Tahun 1974 Tentang Perkawinan) - . Baharudin (Universitas Bandar Lampung (UBL), 2011)
The legal implication from difference religion marriage (lslam law and Marriage Law No.l year 1974 perspective), there is no reason whatever thut dilference religion marriage can at agree, because Islam law and Marriage Law No.l year 1971 perspective is prohibit, therefore, if happen difference religion marriage, so the marriage status not valid, so also with child status. wtlhout the valid difference religion marriage, so bring consequence to wards marriage license, divorce, iheritance, death and ratification birdhs Â child certificate. The diference religion marriage contain risk towards soul development, because many factors that be marriage confict, well- being in one of also the two so also with lhe children soul developmentÂ also will have towards society environment,because marriage not only involve two individual but also deliver family and society,nation and country.